Information mining capabilities in Malaysian SMEs: specific use of enterprise resource planning system - Zulkifli, N.; Hashim, R.; Ahmad, J. (2012)
Information mining has never been more crucial in organizational decision making than now. Without information and communication technologies (ICTs), most companies, particularly the small and medium enterprises (SMEs) would not be able to survive the demands of the current volatile economic conditions. Hence, this paper reports the findings from the assessment of ICT usage by 110 SMEs in the Klang Valley, Malaysia. Specifically, the usage of enterprise resource planning system (ERP) was assessed and the outcome showed that SMEs in Malaysia are still lagging in computer usage for improved organizational decision. The implications for non-usage bode negatively for SME’s sustained survival although the government continued to offer assistance through the annual budget allocation. The findings of this study showed that the perceived ease of use and perceived usefulness had significant relationship with the ERP system usage. A strong and visionary leader would provide the basis to push the SMEs to achieve better returns of investment.